The Analysis of Phonemes in the Duri Dialect and the Pattinjo Dialect : A Descriptive Study of Segmental Phonemes in the Duri and Pattinjo Dialects - Yukir, Muh; Ambo Dalle; Zulfah; Mujahidah; Sunubi, Abdul Haris (IAIN KENDARI, 2025)
This research aims to conduct phoneme analysis in the Duri dialect and the Pattinjo dialect, two dialects located in South Sulawesi, Indonesia. With a focus on analyzing the phonemes between these two dialects, this research examines the linguistic variations that emerge in the northern Enrekang and Pinrang regions. The Duri dialect is located in the Enrekang region, while the Pattinjo dialect dominates the northern Pinrang area. The research method involved collecting data from local informants speaking both dialects, as well as phonematic analysis to identify phoneme differences and similarities between the two. The results of this research provide in- depth insight into the unique phoneme characteristics of each dialect, enriching our understanding of the region's linguistic diversity. This research can contribute to the regional linguistic literature and provide a basis for further research on language variation in South Sulawesi.